Hitchcock Lost and Found : the Forgotten Films. - Kerzoncuf, Alain (Screen Classics., 2015)
Known as the celebrated director of critical and commercial successes such as Psycho (1960) and The Birds (1963), Alfred Hitchcock is famous for his distinctive visual style and signature motifs. While recent books and articles discussing his life and work focus on the production and philosophy of his iconic Hollywood-era films like Notorious (1946) and Vertigo (1958), Hitchcock Lost and Found moves beyond these seminal works to explore forgotten, incomplete, lost, and recovered productions from all stages of his career, including his early years in Britain. Authors Alain Kerzoncuf and Cha.